Gospels or biographies? the Gospels as folk literature - Wishart, Ryder A. (Leiden Boston Brill, 2024)
"Challenging the widely accepted classification of the canonical gospels as biographies or historiographies, the author argues that they should be classified as collections of folk literature from early Christianity. Drawing on comparative register analysis and re-introducing literary and sociolinguistic insights from the twentieth-century form critics, this insightful study challenges readers to rethink the significance of gospels for understanding Jesus's historical context and relevance for modern readers. The gospels are not merely designed to inform readers about the life of Jesus but also to push readers into accepting or rejecting his teaching. It is a must-read for anyone seeking a deeper understanding of the gospel genre and the intentions of the evangelists who compiled them"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Language, style; Bible as literature; Folk literature